Raising the profile of oral language use in Modern Foreign Languages to enhance student engagement in speaking activities - Dixon, Hannah (2016)
Oral language use is undoubtedly a key feature in the study of a modern foreign language. However, the importance of oral language use is not always reflected in students’ attitudes towards language learning. The purpose of this research project was to seek to enhance the value that students in a mainstream comprehensive school give to oral activities to develop their engagement and progression. The literature highlighted motivation as a key factor that impacts on a student’s involvement in a task; with attitudes, task value and feedback all affecting motivation. With these influences in mind, I developed four different oral, communicative tasks, which were designed to enhance student engagement. The research consisted of questionnaires and semi-structured interviews that were conducted on completion of each oral task with a Year 8 Spanish class. The multi-techniques were used to evaluate how effective these tasks were in raising the profile of oral language use. The findings show that the tasks were effective in increasing motivation and engagement with the focus class. The key ideas in the findings were the importance of task variety and inclusion of different forms of feedback. This research has prompted areas for further study, specifically to develop and trial a wider range of speaking tasks with a greater variety of students.